Vibration and torsion-facilitated interactions in para- and meta-disubstituted benzenes - Kemp, David J. (2020)
Intramolecular vibrational (energy) redistribution (IVR) has been a point of discussion in monosubstituted and para-disubstituted benzene molecules for some time, with studies drawing comparisons between related molecules in order to understand the factors that influence the rate at which coupling between vibrational and torsional coordinates is seen. The presence of the methyl rotor, such as in para-fluorotoluene, greatly increases the number of available internal energy levels such that the rate of IVR is expected to increase. It has been suggested, however, that the density of states is not the only factor that causes increased rates of coupling, but small differences in quantum numbers, and thus similarity in character between two states, must also be observed for efficient coupling to occur. Further to this, barriers to internal rotation can be shown to directly affect the positions of the rotor levels, with electronic structure differences between molecules also expected to induce additional changes to vibrational or torsional levels. The expected result of this is that these levels may shift further from, or closer to other levels that may efficiently couple to them.